Case report: Omphalitis caused by Trueperella pyogenes infection in a Korean indigenous calf - Kim, Youngjun; Ji, Min-Jeong; Park, Jinho; Choi, Kyoung-Seong (Frontiers in Veterinary Science, 2024)
Omphalitis, commonly caused by opportunistic bacteria has been significantly associated with morbidity and mortality in neonatal calves. Trueperella pyogenes is a commensal and opportunistic pathogen that can cause suppurative infection in farm animals. Our case involved a 10-day-old female Korean indigenous calf that presented with umbilical enlargement accompanied by a greenish-yellow purulent discharge and right forelimb lameness. The calf was diagnosed with failure of passive transfer at 24 h of age. Physical examination found hypothermia (38.1°C), tachycardia (110 beats/min), tachypnea (47 cycles/min), and open mouth breathing. Ultrasonography revealed hyperechoic pus in the 9th and 10th right intercostals, for which a liver abscess due to omphalophlebitis was suspected. After 3 days, the calf died. T. pyogenes was detected in the umbilical cord, lung, liver, kidney, intestine, mesenteric lymph node, urinary bladder, and bladder ligament. All genes related to the virulent factors (i.e., plo, cbpA, fimA, fimC, fimG, nanH, and nanP) were also identified, with plo and fimA being associated with pathogenicity. A final diagnosis of omphalitis was established based on the identification of virulent T. pyogenes and umbilical cord dilatation on ultrasonography. Antimicrobial susceptibility tests showed that the isolated T. pyogenes was susceptible to amoxicillin, ceftiofur, florfenicol, enrofloxacin, ofloxacin, and ciprofloxacin, suggesting the suitability of these antibiotics for treating T. pyogenes-induced omphalitis. Hence, accurate and rapid diagnosis of the involved bacteria and antimicrobial susceptibility patterns can help guide therapeutic decisions. Our case provides useful information that could aid large animal clinicians in the diagnosis and treatment of T. pyogenes-induced omphalitis.